Comparison between traditional and reverse periodization: Swimming performance and specific strength values - Arroyo-Toledo, J. J.; Clemente, V. J.; González-Rave, J. M.; Domingo J.; Campo, R.; Sortwell, A. D. (International Journal of Swimming Kinetics, 2013)
Periodization of athletic training is conceptualized as a pedagogical process, which involves varying volume, intensity and frequency of training in attempt to optimize sporting performance. The primary purpose of this research was to compare changes in 100m swim performance (t100c), specific swim power output (SSP) and maximum drag charge (MDC), after 14 weeks of training traditional periodization (control) and reverse periodization (treatment). There were 26 volunteer swimmers (16.02±0.6 yrs. 1.72±9.3 cm 64.1±9.3 kg) divided in two groups traditional periodization (TP) and reverse periodization (RP). Results at the 14th week showed significant improvements (p<0.05) in values of t100c (6.9%), SSP (20.9%) and MDC (10.0%) by RP above TP values. The results demonstrated that reverse periodization is specific and an efficient strategy of training for sprinters at time to reduce significantly load volume.